IMPLEMENTING VISUALIZATION, AUDITORY, KINESTETIC (VAK) LEARNING MODEL TO IMPROVE STUDENTS’ CREATIVE THINKING ABILITIES IN SCIENCE SUBJECT - Ayu Fiyanti Rahmadani; Nana Hendracipta; Encep Andriana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was a quantitative study with a quasi-experimental research type. The purpose of this study was to determine the differences in creative thinking skills between students taught by visualization, auditory, kinesthetic (VAK) model and students taught by direct learning model. This research was conducted at grade IV SDN 2 Pagelaran. The data collection technique was done by testing. The main instrument in this research was a test of students' creative thinking skills. Then, data were analyzed through descriptive statistic data and inferential statistical data. The posttest results revealed that the average score of students' creative thinking skills in the experimental class was 68.8, while the average score in the control class was 58.6. It was seen from the average difference test that the comparison of the testing criteria was tcount ≥ ttable or 4.41 ≥ 2.019. From the results, it was stated that there was a difference in students' creative thinking abilities between the control class and the experimental class. After that, it was also tested with the right side test in which tcount ≥ ttable or 4.09 ≥ 1.671, with a significant level of 0.05. Based on the results, it was concluded that the students had better creative thinking abilities after being taught by visualization, auditory, kinesthetic (VAK) model than students taught by direct learning model.